2020
DOI: 10.31258/ijesh.2.2.79-90
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Islamic Corporate Governance Towards Financial Performance (Empirical Study on Sharia Commercial Banks in Indonesia Year 2013-2017)

Abstract: This study aims to find empirical evidence of the Islamic corporate governance mechanism influence the institutional ownership, commissioner board proportion, a board of independent commissioners, the sharia supervisory board proportion, and the audit committee on financial performance. The population of this study is Sharia Commercial Bank in Indonesia year 2013-2017. The population is 13 Sharia Commercial Banks. The sampling technique in this study used a purposive sampling technique. This study obtained 9 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Previous researchers found the Sharia Supervisory Board (SSB) affected financial performance (Aslam & Haron, 2020;Hanifah & Syafruddin, 2020;Hassan et al, 2017;Hisamuddin & Tirta K, 2015). While the other researchers stated, the Sharia Supervisory Board did not affect financial performance (Eksandy, 2018;Muchtar et al, 2020;Nasution & Nasrizal, 2020;Savitri et al, 2020). According to the phenomenon and research gap explained, this research aims to continue the empirical studies.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous researchers found the Sharia Supervisory Board (SSB) affected financial performance (Aslam & Haron, 2020;Hanifah & Syafruddin, 2020;Hassan et al, 2017;Hisamuddin & Tirta K, 2015). While the other researchers stated, the Sharia Supervisory Board did not affect financial performance (Eksandy, 2018;Muchtar et al, 2020;Nasution & Nasrizal, 2020;Savitri et al, 2020). According to the phenomenon and research gap explained, this research aims to continue the empirical studies.…”
Section: Introductionmentioning
confidence: 89%
“…Kusuma & Ayumardani, 2016). However, the other studies found there was no significant effect of the Board of Commissioner on the financial performance (M. Kusuma & Rosadi, 2019;Muchtar et al, 2020;Nasution & Nasrizal, 2020;Savitri et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation